The impact of oral vitamin A derivatives on lipid metabolism: what recommendations can be derived for dealing with this issue in the daily dermatological practice? - Klör, Hans-Ulrich; Weizel, Achim; Augustin, Matthias; Diepgen, Thomas L.; Elsner, Peter; Homey, Bernhard; Kapp, Alexander; Ruzicka, Thomas; Luger, Thomas A. (Journal der Deutschen Dermatologischen Gesellschaft, 2011)
Retinoids and vitamin A derivatives have been widely used topically and systemically in the treatment of hyper- and parakeratotic skin diseases, genodermatoses, severe acne, autoimmune diseases (i. e. lupus erythematosus) or cutaneous T-cell lymphoma for more than 30 years. In addition to the desired proliferation-inhibiting, differentiation-inducing and antiinflammatory or sebo-suppressive effects, vitamin A derivatives also affect lipid metabolism. This is shown primarily by an increase of transaminases, triglycerides or cholesterol levels which vary in intensity from patient to patient. The degree of impact on the different parameters of lipid metabolism depends on the nature of the vitamin A derivative on the one hand due to different receptor specific binding interactions (RAR/RXR), while on the other hand posttranslational processes also play a major role. This review paper gives a brief, concise overview of the vitamin A derivatives and possible effects on lipid metabolism that can be expected. Additionally it contains a recommendation for secure handling of abnormal laboratory values before, during and after oral therapy with vitamin A derivatives. The aim of this article is to provide practical help and confidence in dealing with vitamin A derivatives in daily clinical practice. The publication was created in cooperation with the Deutsche Dermatologische Gesellschaft (DDG) and Deutsche Gesellschaft zur Bekämpfung von Fettstoffwechselstörungen und ihren Folgeerkrankungen (DGFF [Lipid-Liga] e. V.).
Gesehen am 19.09.2022